(untitled) (Mokslo taikomieji tyrimai / Applied Research, 2019)
During the inactivation of various organic wastes by conventional thermal methods (distillation, desorption), the process temperature is lower than 1300-15000 C. However, this is not sufficient for proper decomposition of waste materials. For the complete decomposition of such materials, the reaction temperature should be raised to 18000 C. This article aims to determine the temperature and velocity profile distributions of the high-temperature gas flow inside the plasma reactor. According to the study, the plasma-chemical method for decomposition of sewage sludge is quite effective. The efficiency of the gas-phase sludge decomposition depends on the plasma flow parameters (temperature, velocity, etc.).